A guide to the collision avoidance rules international regulations for preventing collisions at sea - Cockcroft, A. N. (Elsevier, 2012)
A Guide to the Collision Avoidance Rules is the essential reference to the safe operation of all vessels at sea. Published continuously since 1965, this respected and expert guide is the classic text for all who need to practically and legally understand and comply with 'The Rules'. This seventh edition includes the full text of the International Regulations for Preventing Collisions at Sea, with practical discussion of the implications of the rules included alongside all updates seen over the years, including the most recent amendments which came into force in December 2009. The books sets out the 'COLREGs' with clear explanation of their meaning, and gives detailed examples of how the rules have been used in practice by seafarers, as well as excerpts from court judgments to illustrate how they have been interpreted in practice. Written for seagoing engineers, navigating officers, senior crew, cadets and those in training, plus ship operators, marine lawyers and anyone concerned with the safe operation of shipping, this is an essential reference at sea and on shore. Includes the full text of the International Regulations for Preventing Collisions at Sea, updated in line with the December 2009 amendments to the rules. Contains practical advice on how the regulations should be interpreted and collisions avoided, with insightful discussion of the implications of key phrases and Court interpretations. Covers important maneuvering information, with diagrams covering stopping distances, turning circles of ships of various type and size, and a color section with examples of ships' lights.
"Incorporating the 1981, 1987, 1989, 1993, 2001 and 2007 amendments."
Includes index.
Keywords: Rule of the road at sea.; Collisions at sea.; elektronické knihy; electronic books